EphB4 as a therapeutic target in mesothelioma - Liu, Ren (BioMed Central, 2013)
BACKGROUND: Malignant pleural mesothelioma (MPM) often develops decades following exposure to asbestos. Current best therapy produces a response in only half of patients, and the median survival with this therapy remains under a year. A search for novel targets and therapeutics is underway, and recently identified targets include VEGF, Notch, and EphB4-Ephrin-B2. Each of these targets has dual activity, promoting tumor cell growth as well as tumor angiogenesis. METHODS: We investigated EphB4 expression in 39 human mesothelioma tissues by immunohistochemistry. Xenograft tumors established with human mesothelioma cells were treated with an EphB4 inhibitor (monomeric soluble EphB4 fused to human serum albumin, or sEphB4-HSA). The combinatorial effect of sEphB4-HSA and biologic agent was also studied. RESULTS: EphB4 was overexpressed in 72% of mesothelioma tissues evaluated, with 85% of epithelioid and 38% of sarcomatoid subtypes demonstrating overexpression. The EphB4 inhibitor sEphB4-HSA was highly active as a single agent to inhibit tumor growth, accompanied by tumor cell apoptosis and inhibition of PI3K and Src signaling. Combination of sEphB4-HSA and the anti-VEGF antibody (Bevacizumab) was superior to each agent alone and led to complete tumor regression. CONCLUSION: EphB4 is a potential therapeutic target in mesothelioma. Clinical investigation of sEphB4-HSA as a single agent and in combination with VEGF inhibitors is warranted.